Aspek Histopatologik Adenokarsinoma Prostat - Erna Kristiani (Medicinus, 2018)
Introduction: Prostate carcinoma is the second most common tumor in male, 95% in which made up from adenocarcinoma. The diagnosis of prostate adenocarcinoma through a needle biopsy specimen plus the determination of tumor staging are paramount in selecting the therapy and management. This study is done to know the morphologic variation of prostate adenocarcinoma in the needle biopsy as well as to measure the grading compatibility between the needle biopsy and prostatectomy using Gleason scoring system.Materials and Method: This retrospective study is conducted through form and specimen slides compilement. The specimens, consisting of prostate adenocarcinoma’s needle biopsy and prostatectomy, were gathered from the archives of Pathological Anatomy Departement, Faculty of Medicine, University of Indonesia in the year of 2008-2013. The slides were re-read and the morphologic appearance’s variation was valued. Gleason scoring was also executed from the pairing specimen according to International Society of Urological Pathology (ISUP) 2010.Result: Out of 114 needle biopsy cases, the morphologic variation was found to be perineural invation (n=38), mucinous fibroplasia (n=1), glomerulation (n=1), mucinous basophilic (n=25), and eosinophilic crystal (n=5). The amount of patient that was performed both specimen is 11, and there is a compatibility between biopsy score and prostatectomy as much as 63.63% and the median is 7.Conclusion: It is requisite to know the morphological variation in prostate adenocarcinoma in the biopsy needle specimen to get an accurate diagnosis. Undergrading in biopsy specimen is as much as 36.36%, owing to the fact that prostate carcinoma can be manifested as mutifocal lesion, thus the higher grading can only be found in prostatectomy specimen, for the needle biopsy was inadequately taken.Keywords: prostate adenocarcinoma, morphological view, Gleason score